Student academic performance outcomes of a classroom physical activity ıntervention: A pilot study - Heather Erwin; Alicia Fedewa; Soyeon Ahn (International Electronic Journal of Elementary Education, 2012)
A Physical activity is beneficial to children’s health, yet academic pressures limit opportunities for students throughout the school day. The purpose of this study was to determine the effect of a classroom PA intervention on student academic performance outcomes. Intervention participants (n=15) received daily PA breaks. Reading and mathematics fluency, PA, grades, and standardized test scores were collected. Effects of the intervention were examined using mixed-design ANOVAs. Intervention students had significantly higher reading fluency and mathematics scores post-intervention and higher means for standardized reading and mathematics scores as well as grades. Short bouts of PA are important for improving CBM math and reading fluency scores. Classroom teachers should be encouraged to devote time during academic learning to incorporate PA.